2017
DOI: 10.1016/j.apgeog.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A spatial analytic approach for classifying greenspace and comparing greenspace social equity

Abstract: Urban planners frequently adhere to 'park minimum standards' to ensure that public health and environmental benefits associated with greenspace are socially equitable. These standards denote the extent and placement of greenspaces, but rarely consider their form and function. Arguably, an inclusive evaluation of greenspace social equity requires the comparison of greenspace types. To address if greenspace types are socially equitable, I develop a novel spatial analytic approach that classifies 4,265 greenspace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 83 publications
(89 reference statements)
3
36
0
5
Order By: Relevance
“…It is also useful to prioritize which category of urban green space that needs attention to improve their quality and quantity as well as to protect them from any land use development. In fact, studies by Kimpton (2017) in a capital city of Australia revealed that employing systematic classification of urban green spaces can improve our understanding of the association between social equity and urban green spaces provision. Thus, this kind of information are crucial in formulating urban development policy which ultimately to achieve sustainable urban development.…”
Section: Discussionmentioning
confidence: 99%
“…It is also useful to prioritize which category of urban green space that needs attention to improve their quality and quantity as well as to protect them from any land use development. In fact, studies by Kimpton (2017) in a capital city of Australia revealed that employing systematic classification of urban green spaces can improve our understanding of the association between social equity and urban green spaces provision. Thus, this kind of information are crucial in formulating urban development policy which ultimately to achieve sustainable urban development.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the narratives used to explain the importance of justice in greenspace, we found that most researchers frame justice concerns from an ethical and fairness perspective [34,[39][40][41]45,46,52]. However, we identified variation based on the disciplinary perspective.…”
Section: Recognitionmentioning
confidence: 93%
“…Other disciplines look at both types of justice. For example, park managers examine the spatial distribution of greenspace [45,46], with some attention to community participation, which corresponds to procedural justice [44]. Also, urban planners examine justice mostly in terms of distribution, both spatial and temporal [35][36][37] with some procedural focus on decision-making and power asymmetries [37].…”
Section: Distribution and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, precise application of the 'availability' or 'access' measure is a prerequisite for appropriate diagnosis of (potentially) existing inequality in UGS distribution. Kimpton (2017), after testing different measures of accessibility, concluded that choice of access measure might influence the relationship between access and socio-economic indicators. Hence, studies which focus on the development of appropriate measures or indicators of availability and accessibility of UGS are an important part of EJ research worldwide (Van Herzele, Wiedemann, 2003;Comber, Brunsdon, Green, 2008;La Rosa, 2014;Raymond et al, 2016;Koprowska et al, 2018;.…”
Section: Urban Green Space Availability and Environmental Justicementioning
confidence: 99%